Experimental and numerical study of the relative humidity effect on drying shrinkage and cracking of self-consolidating concrete. (January 2019) - Samouh, Hamza; Rozière, Emmanuel; Loukili, Ahmed
Abstract: The drying shrinkage of cementitious materials is a complex phenomenon that is very sensitive to boundary conditions such as relative humidity (RH). Its evolution in the range of high RH is well-known and strongly related to the capillary pressures. However, for a range of lower RH, the pressures induced by interfaces become more significant and the behavior less predictable and needs to be better understood. An experimental study is presented in this paper for which free and restrained shrinkages were measured on self-consolidating concrete for three different relative humidities: 30%, 50% and 70%. A maximum value of drying shrinkage was observed for the intermediate relative humidity. This result can be partly explained by the hydration-drying coupling at the lowest relative humidity and its effect on desorption isotherm. This was experimentally confirmed by shrinkage vs. mass loss evolution, mercury intrusion porosimetry tests and numerically by shrinkage modeling. The first model takes into account the different physical phenomena involved in shrinkage. It allows reproducing the evolution of drying shrinkage and deducing desorption isotherm for each material. Under the most severe studied condition, cracking sensitivity was the highest. The second model takes into account the aging viscoelastic behavior of material to estimate the stresses induced by restrained shrinkage. Among the concrete properties which influence cracking, the shrinkage rate appeared as a major parameter.